Research on the measurement and spatiotemporal evolution characteristics of new quality productive forces in China’s marine economy - Jin, Xue; Wang, Yanwei; Yin, Kedong (Frontiers in Marine Science, 2024)
The marine economy's new quality productive forces is an important driving force to promote the high-quality development of the marine economy. Exploring the level of marine economy's new quality productive forces and its spatiotemporal evolution law will help to provide solid theoretical support and empirical basis for formulating scientific strategies to promote the accelerated development of marine economy. This paper takes the marine economy's new quality productivity as the starting point, explores its spatiotemporal evolution process by measuring its level, finds its shortcomings in promoting the development of marine economy, and provides policy suggestions for the development of marine economy.